Implementation of Pressure Loss Model for Incompressible Flow Solver on Cartesian Grid Method - AKASAKA, Kei; ONO, Kenji (Transactions of the Japan Society for Computational Engineering and Science, 2007)
The Cartesian grid method is very useful for CFD simulation around a complex geometry in terms of automatic and robust grid generation. However, it is difficult to simulate both large-scale and subgrid-scale flow simultaneously on the Cartesian grid because of the restriction of a computing resource. Therefore, an empirical formula is often employed on the Cartesian grid system to incorporate the subgrid-scale effect of fluid characteristics. For example, in the case of flow computation for heat exchangers, the detail of geometry is usually not represented. Instead, Darcy’s law is used to simulate the relationship between flow rate and pressure drop. Moreover, for the flow calculation around the unaligned heat exchanger with respect to the underlying Cartesian grid, a special technique is necessary to express the pressure drop along the normal direction of the inclined heat exchanger. In this paper, the empirical formula that describes macroscopic fluid properties is expressed as an external force in the incompressible Navier-Stokes equations. This formulation is also valid for unaligned heat exchangers. Special attention is paid to the iterative method of the pressure Poisson equation in order to satisfy the constraint of the fluid characteristics for the heat exchanger. To validate the proposed method, several examples were calculated. Finally, it was found that the proposed method could reasonably predict the pressure loss of the inclined heat exchanger. In addition, the convergence behavior of the iterative process was investigated.